Meta-nested

Algebra Level 4

f = 1 + 3 + 1 + 3 + 2 + 3 + 1 + 3 + 2 + 2 + 2 + 1 + 1 + 3 + 2 + = A B \Large f=1+\dfrac{3+\dfrac{1+ \frac{3+\cdots}{2+\cdots}}{3+ \frac{1+\cdots}{3+\cdots}}} { 2+\dfrac{2+\frac{2+\cdots}{1+\cdots}}{1+ \frac{3+\cdots}{2+\cdots}}}=\dfrac{A}{B}

Find the value of A + B A+B , where A A and B B are coprime.


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Gabriel Chacón
Apr 9, 2019

f = 1 + 3 + 1 + 3 + 2 + 3 + 1 + 3 + 2 + 2 + 2 + 1 + 1 + 3 + 2 + = A B f=1+ \dfrac{\color{#3D99F6} 3+\dfrac{1+ \frac{3+\cdots}{2+\cdots}}{3+ \frac{1+\cdots}{3+\cdots}} } { \color{#D61F06} 2+\dfrac{2+\frac{2+\cdots}{1+\cdots}}{1+ \frac{3+\cdots}{2+\cdots}}} =\dfrac{A}{B}

Define g = 3 + 1 + 3 + 2 + 3 + 1 + 3 + \color{#3D99F6} g= 3+\dfrac{1+ \frac{3+\cdots}{2+\cdots}}{3+ \frac{1+\cdots}{3+\cdots}} and h = 2 + 2 + 2 + 1 + 1 + 3 + 2 + \color{#D61F06} h= 2+\dfrac{2+\frac{2+\cdots}{1+\cdots}}{1+ \frac{3+\cdots}{2+\cdots}}

We now have the equations:

g = 3 + f g f = g ( g 3 ) g=3+\dfrac{f}{g} \implies f=g(g-3)

h = 2 + h f 1 h = 1 2 + 1 2 f 1 h = 1 2 + 1 2 g ( g 3 ) h=2+\dfrac{h}{f} \implies \dfrac{1}{h}=\dfrac{1}{2}+\dfrac{1}{2f} \implies \dfrac{1}{h}=\dfrac{1}{2}+\dfrac{1}{2g(g-3)}

f = 1 + g h g ( g 3 ) = 1 + g ( 1 2 + 1 2 g ( g 3 ) ) 2 g 3 13 g 2 + 19 g + 7 = 0 f=1+\dfrac{g}{h} \implies g(g-3)=1+g \left( \dfrac{1}{2}+\dfrac{1}{2g(g-3)} \right) \implies 2g^3-13g^2+19g+7=0

This 3rd-degree polynomial on g g has three real solutions, but only one of them, g = 7 2 g=\frac{7}{2} , leads to a value of f > 1 f>1 .

The solution is f = 7 4 f=\dfrac{7}{4} and the answer is A = 7 , B = 4 A=7, B=4 and A + B = 11 \boxed{A+B=11} .

Nice question! I solved it a similar way, but left g g and h h in terms of f f , so g = 3 ± 9 + 4 f 2 g = \frac{3 \pm \sqrt{9 + 4f}}{2} and h = 2 f f 1 h = \frac{2f}{f - 1} . Then f = 1 + g h f = 1 + \frac{g}{h} solves to 4 f ( f 1 ) f 1 3 = ± 9 + 4 f \frac{4f(f - 1)}{f - 1} - 3 = \pm \sqrt{9 + 4f} , and the ( f 1 ) (f - 1) terms can be eliminated since f > 1 f > 1 , leaving the quadratic equation ( 4 f 3 ) 2 = 9 + 4 f (4f - 3)^2 = 9 + 4f (instead of a cubic equation) which also solves to f = 7 4 f = \frac{7}{4} for f > 1 f > 1 .

David Vreken - 2 years, 2 months ago

Log in to reply

It is definitely easier to find the value of f f your way. In my case, knowing that the answer for g g was also a rational number, I was able to find the root after a couple of lucky guesses using Ruffini's rule.

Gabriel Chacón - 2 years, 2 months ago

Note that you have to substantiate why f , g , h f, g, h are not zero or infinity, in order to multiply throughout and still have the equation hold true.

Calvin Lin Staff - 2 years, 2 months ago

How is g-3=f/g? And why is congruence sign used while defining 'g' and 'h', is it typing mistake?

Mr. India - 2 years, 1 month ago

Log in to reply

Add one more level in the denominator of the blue expression: g = 3 + 1 + 3 + 2 + = f 3 + 1 + 3 + 2 + 3 + 1 + 3 + = g g= 3+\dfrac{\boxed{1+ \frac{3+\cdots}{2+\cdots} } =f}{\boxed{ 3+ \frac{1+ \frac{3+\cdots}{2+\cdots} }{ 3+ \frac{1+\cdots}{3+\cdots} } }=g } . The congruence sign is definitely not the symbol to be used here, there shoud be an : = := sign or just an = = sign. I've fixed it.

Gabriel Chacón - 2 years, 1 month ago
Anirudh Sreekumar
Apr 10, 2019

f = 1 + 3 + 1 + 3 + 2 + 3 + 1 + 3 + 2 + 2 + 2 + 1 + 1 + 2 + 2 + = A B Let, f = 1 + x y ( 1 ) where, x = 3 + 1 + 3 + 2 + 3 + 1 + 3 + and y = 2 + 2 + 2 + 1 + 1 + 3 + 2 + ( y 2 ) = y f f ( y 2 ) = y y ( f 1 ) = 2 f y x y = 2 f From ( 1 ) x = 2 f ( 2 ) , y > 2 x = 3 + 1 + 3 + 2 + 3 + 1 + 3 + x = 3 + f x 2 f = 3 + f 2 f From ( 2 ) 2 f = 3 + 1 2 f > 1 2 f = 7 2 f = 7 4 A B = 7 4 A + B = 11 \begin{aligned} f&=1+\dfrac{3+\dfrac{1+\dfrac{3+\cdots}{2+\cdots}}{3+\dfrac{1+\cdots}{3+\cdots}}}{2+\dfrac{2+\dfrac{2+\cdots}{1+\cdots}}{1+\dfrac{2+\cdots}{2+\cdots}}}=\dfrac{A}{B}\\ \text{Let,}\\ f&=1+\dfrac{x}{y} \hspace{4mm}\color{#3D99F6}\small(1) \\ \text{ where,}\\ x&=3+\dfrac{1+\dfrac{3+\cdots}{2+\cdots}}{3+\dfrac{1+\cdots}{3+\cdots}}\\\\ \text{and }y&=2+\dfrac{2+\dfrac{2+\cdots}{1+\cdots}}{1+\dfrac{3+\cdots}{2+\cdots}}\\ (y-2)&=\dfrac{y}{f}\\ \implies f(y-2)&=y\\ y(f-1)&=2f\\ y\cdot\dfrac{x}{y}&=2f \hspace{4mm}\color{#3D99F6}\small\text{From}(1)\\ \implies x&=2f\hspace{4mm}\color{#3D99F6}\small(2) \hspace{8mm},y>2\\\\ x&=3+\dfrac{1+\dfrac{3+\cdots}{2+\cdots}}{3+\dfrac{1+\cdots}{3+\cdots}}\\ x&=3+\dfrac{f}{x}\\ 2f&=3+\dfrac{f}{2f}\hspace{4mm}\color{#3D99F6}\small\text{From }(2)\\ 2f&=3+\dfrac{1}{2}\hspace{4mm}\color{#3D99F6}\small f>1\\ 2f&=\dfrac{7}{2}\\ f&=\dfrac{7}{4}\\ \dfrac{A}{B}&=\dfrac{7}{4}\\ \implies A+B&=\color{#EC7300}\boxed{\color{#333333}11} \end{aligned}

Nice and simple solution!

Gabriel Chacón - 2 years, 2 months ago

Log in to reply

Thank you! :)

Anirudh Sreekumar - 2 years, 1 month ago
Eric Nordstrom
Apr 12, 2019
  1. f = 1 + x y f=1+\frac{x}{y}
  2. x = 3 + f x x=3+\frac{f}{x}
  3. y = 2 + y f y=2+\frac{y}{f}

Solving Eq. 2 for x x gives

x 2 3 x f = 0 x = 3 ± 9 + 4 x 2 x^2-3x-f=0\\ x=\frac{3\pm \sqrt{9+4x}}{2} .

x x must be positive, and 9 + 4 x > 3 \sqrt{9+4x}>3 , so

x = 3 + 9 + 4 x 2 \bf x=\frac{3+\sqrt{9+4x}}{2} .

Solving Eq. 3 for y y gives

y = 2 1 1 f \bf y=\frac{2}{1-\frac{1}{f}} .

Inserting these expressions into Eq. 1 and solving for f f goes as follows:

f = 1 + ( 3 + 9 + 4 f 2 ) ( 2 1 1 f ) 4 ( f 1 ) = ( 1 1 f ) ( 3 + 9 + 4 f ) 4 f ( f 1 ) = ( 3 + 9 + 4 f ) ( f 1 ) f = 1 or 4 f = 3 + 9 + 4 f f=1+\frac{\left(\frac{3+\sqrt{9+4f}}{2}\right)}{\left(\frac{2}{1-\frac{1}{f}}\right)}\\ 4(f-1)=(1-\frac{1}{f})(3+\sqrt{9+4f})\\ 4f(f-1)=(3+\sqrt{9+4f})(f-1)\\ \bf f=1\text{ or } 4f=3+\sqrt{9+4f}

If f = 1 f=1 , then y y is undefined, so 4 f = 3 + 9 + 4 f \bf 4f=3+\sqrt{9+4f} . Therefore,

( 4 f 3 ) 2 = 9 + 4 f 16 f 2 28 f = 0 f = 0 or f = 7 4 (4f-3)^2=9+4f\\ 16f^2-28f=0\\ \bf f=0\text{ or }f=\frac{7}{4} .

f f is clearly a positive number, so f = 7 4 f=\boxed{\bf \frac{7}{4}} . Since 7 and 4 are coprime, A = 7 A=7 and B = 4 B=4 , so A + B = 11 A+B=\boxed{\bf 11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...